Physiological characteristics of elite high‐altitude climbers. Issue 9 (27th August 2015) - Puthon, L.; Bouzat, P.; Rupp, T.; Robach, P.; Favre‐Juvin, A.; Verges, S.
Abstract : Factors underlying the amplitude of exercise performance reduction at altitude and the development of high‐altitude illnesses are not completely understood. To better describe these mechanisms, we assessed cardiorespiratory and tissue oxygenation responses to hypoxia in elite high‐altitude climbers. Eleven high‐altitude climbers were matched with 11 non‐climber trained controls according to gender, age, and fitness level (maximal oxygen consumption, VO2 max ). Subjects performed two maximal incremental cycling tests, in normoxia and in hypoxia (inspiratory oxygen fraction: 0.12). Cardiorespiratory measurements and tissue (cerebral and muscle) oxygenation were assessed continuously. Hypoxic ventilatory and cardiac responses were determined at rest and during exercise; hypercapnic ventilatory response was determined at rest. In hypoxia, climbers exhibited similar reductions to controls in VO2 max (climbers −39 ± 7% vs controls −39 ± 9%), maximal power output (−27 ± 5% vs −26 ± 4%), and arterial oxygen saturation (SpO2 ). However, climbers had lower hypoxic ventilatory response during exercise (1.7 ± 0.5 vs 2.6 ± 0.7 L/min/%; P < 0.05) and lower hypercapnic ventilatory response (1.8 ± 1.4 vs 3.8 ± 2.5 mL/min/mmHg; P < 0.05). Finally, climbers exhibited slower breathing frequency, larger tidal volume and larger muscle oxygenation index. These results suggest that elite climbers show some specific ventilatory and muscular responses to hypoxia possibly because of genetic factors or adaptation to frequent high‐altitude climbing.